VARIOS. (1982). Antología y comentario de textos de Filosofía. Curso de Orientación Universitaria. Madrid: Editorial Alhambra S. A. 685 págs. - Gaitán Riveros, Carlos; Pontificia Universidad Javeriana (2016)
null